Analisis Akar Masalah terhadap Rendahnya Hasil Belajar Menulis Teks Deskripsi Siswa Kelas IV SD - Syifa Auliani; Chandra Chandra; Salmaini Safitri Syam (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to identify and understand the root causes of low student learning outcomes in writing descriptive texts in grade IV of elementary school. Based on the results of field observations, it was found that the majority of students scored below the Minimum Completion Criteria (KKM) in both cognitive and psychomotor aspects. In addition, student participation in learning activities is also relatively low, which is reflected in minimal interaction, lack of discipline, and lack of self-expression. This study uses a descriptive method with a qualitative approach, using observations in the form of tests and documentation as data collection techniques. The results of the study indicate that lack of understanding of the structure and characteristics of descriptive texts, interaction in learning, challenges in using learning media, and low student motivation are dominant factors in decreasing the quality of learning outcomes. Other factors are low interest in reading and limited student vocabulary. This study recommends that learning be carried out with a more communicative, applicable, and meaningful approach according to the characteristics of students in elementary schools.